2021
DOI: 10.3390/ijerph182412986
|View full text |Cite
|
Sign up to set email alerts
|

Explaining News Trust in Social Media News during the COVID-19 Pandemic—The Role of a Need for Cognition and News Engagement

Abstract: During the recent COVID-19 pandemic, people have, in many cases, acquired information primarily from social media. Users’ need to stay informed and the intensive circulation of news has led to the spread of misinformation. As they have engaged in news, it has raised the question of trust. This study provides a model on how news trust can be explained through a need for cognition and news engagement. Accordingly, 433 Slovenian social media users participated in our survey. Structural equation modeling revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…News engagement reflects the means by which audiences consume and participate in the news for either personal or social purpose (Ha et al, 2018; Park et al, 2021). A conceptual model for the relationship between NFC, news engagement, and news trust constructed for social media platforms was developed (Kožuh and Čakš, 2021) examining the mediating effects of news engagement on the relationship between the NFC and news trust. According to the model, the lower the NFC and the more prior knowledge social media users have about COVID-19, the more likely they think social media news includes all the essential facts about COVID-19 (Kožuh and Čakš, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…News engagement reflects the means by which audiences consume and participate in the news for either personal or social purpose (Ha et al, 2018; Park et al, 2021). A conceptual model for the relationship between NFC, news engagement, and news trust constructed for social media platforms was developed (Kožuh and Čakš, 2021) examining the mediating effects of news engagement on the relationship between the NFC and news trust. According to the model, the lower the NFC and the more prior knowledge social media users have about COVID-19, the more likely they think social media news includes all the essential facts about COVID-19 (Kožuh and Čakš, 2021).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, trust plays a crucial role in social media; thus, this variable must be studied by academics [36,37]. Based on Kožuh and Čakš [38], social media is one of the credible sources of information in a health crisis. In addition, according to Jin et al [39], user's willingness to share and adopt health knowledge is dependent on their trust in social media.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, according to Jin et al [39], user's willingness to share and adopt health knowledge is dependent on their trust in social media. The more users engage with social media news, the more they trust the actual situation around COVID-19 [38], thereby potentially increasing their self-efficacy and protective behavior. Moreover, trust in social media could influence users' response to comply with COVID-19 protocol guidance [40].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID‐19 pandemic, people have used social media more than ever (Kaya, 2020). However, it is reported that individuals' confidence in science has been shaken due to some news spread on social media during the pandemic (Kozuh & Caks, 2021). Social media shares have been an important part of the unfounded information spreading from the claim that the virus spreads faster with 5G technology (Buarque, 2022) to the fact that drinking pure alcohol is a precaution to be taken against the virus (Van Dijck & Alinejad, 2020).…”
Section: Introductionmentioning
confidence: 99%